Evaluating the effect of "Zumwinkel-Affair" and financial crisis on stock prices in Liechtenstein: An unconventional augmented GARCH-approach - Andreas Brunhart (Universität Liechtenstein, Konjunkturforschungsstelle Liechtenstein (KOFL), 2011)
Liechtenstein's economy has been heavily affected by the international economic downturn during the financial crisis. Additionally to the deep world recession, Liechtenstein's financial sector was challenged by the Zumwinkel-Affair (data of thousands of tax evaders were sold to several international tax authorities by a whistleblower). This paper investigates the impact of this affair, separated from the financial crisis, on the daily stock prices of two banks from Liechtenstein: Verwaltungs- und Privatbank (VPB) and Liechtensteinische Landesbank (LLB). The econometric analysis involves an unconventional augmented GARCH-model to analyse the dynamical pattern and other influences on the risk measured by the conditional variance of the stock returns. To evaluate the impact of financial crisis and Zumwinkel-Affair on risk, additional explaining variables have been incorporated into the (therefore augmented) variance equation. As an additional (yet unconventional) feature the lagged squared residuals have been dropped from the GARCH-specification and replaced by squared lagged observed variables such as past stock returns and past stock market performance (this replacement appears to be the superior specification here). Besides other findings, it is shown that both the financial crisis and the Zumwinkel-Affair have a significant (accumulating) effect on risk/volatility of both stocks, but the impact on the volatility of VPB's stock returns is considerably higher compared to LLB's stocks.
Keywords: C01; C22; C32; G01; G21; 330; Financial Crisis; Tax Affair; Liechtenstein; Financial Institutions; Stock Prices; Stock Price Volatility; Augmented GARCH-models; Augmented Conditional Variance Equation; Finanzmarktkrise; Steuerkriminalität; Börsenkurs; ARCH-Modell; Schätzung; Liechtenstein